(untitled) (Nigerian Journal of Technology, 2020)
This work is on remediation of zinc concentration (330.0 mg/kg) in soils from farm settlement at Agbabu community in Ondo State of Nigeria to below maximum allowable 300 mg/kg specified for safe agriculture by standards to ensure that farm products from this farm settlement close to area of mining are safe for human beings. Three indigenous organisms: Bacillus subtilis (B. subtilis), Escherichia coli (E. coli) and Proteus mirabilis (P. mirabilis) were engaged for the remediation study. The organisms were isolated and cultured. Optimum weights of the distinct organisms were inoculated in 4g soils each conditioned with optimum values of pH, temperature, stirring frequency and nutrient in thirty-six 50 ml beakers; and experimented for residual zinc ion at times 5, 10, 15, 20, 25, 30 and 35 days in triplicate with Atomic Absorption Spectrophotometer. Each organism maintained its performance position from day 5 to day 35. Bacillus subtilis took the lead, seconded by P. mirabilis while E. coli lagged. Removal to safe concentration first occurred at 10 days for B. subtilis, 15 days for P. mirabilis and 20 days for E. coli with respective 292.09 mg/kg, 294.37 mg/kg, and 290. 71 mg/kg residual concentrations. The respective residual concentrations and efficiencies at 35 days were 247.33 mg/kg and 25.06 %; 253.47 mg/kg and 23.20 %; and 267.11 mg/kg and 19.07 %. Two-ways ANOVA at (P < 0.05) showed that a combination of 2 or 3 of the organisms would result in lower residual concentration; and relevant performances at shorter times. http://dx.doi.org/10.4314/njt.v39i2.31